Robust Polyethylenimine Electrolyte for High Performance and Thermally Stable Atomic Switch Memristors. (13th September 2020) - Yang, Dongliang; Yang, Huiyong; Guo, Xiangyu; Zhang, Haitao; Jiao, Chaohui; Xiao, Wei; Guo, Pengqian; Wang, Qi; He, Deyan
Abstract: Organic polymer solid electrolytes show interesting application prospects in resistive switching memories and brain‐inspired computing ionic devices. However, polymer electrolytes can easily decompose under heat treatment and their ionic conductivity can vary significantly at different temperatures. Among the reported polymer memristors, most of them lack sufficient reproducibility, endurance, stability, uniformity, and inter alia heat tolerance. Based on a molecular group that is thermally stable over a large temperature range and a structure with polar bonds for assisted ion migration, herein, a new polymer memristor is demonstrated employing polyethyleneimine (PEI) as a solid electrolyte for the first time. Atomic switch memristors equipped with PEI solid polymer electrolyte exhibit stable resistive switching at room temperature and high temperatures with a good retention, large ON/OFF ratio of 10 5, and stable cycle performance within a temperature range from 25 to 150 °C. The memristors fabricated on a polyimide substrate exhibit excellent switching performance at 150 °C after 2000 bending cycles, illustrating the potential for flexible electronic applications. Structural analysis reveals that the excellent thermally stable switching performance is derived from the stability of the molecular chain and a lower T g (glass transition temperature). Abstract : Thermally stable polyethylenimine is used as the electrolyte in memory devices, which exhibit non‐volatile resistive switching behavior with a stable cycle 10 3 in a DC sweep and a large ON/OFF ratio over 10 5, a long retention time exceeding 10 5 s and a wide working temperature range of 24–150 °C. It also has good switching performance on flexible devices.